Evidence for the Helicity Barrier from Measurements of the Turbulence Transition Range in the Solar Wind - J. R. McIntyre; C. H. K. Chen; J. Squire; R. Meyrand; P. A. Simon (Physical Review X, 2025)
Many hot, diffuse astrophysical plasmas are collisionless, with collision times that exceed dynamical timescales of interest. Without a standard viscosity, the mechanisms by which mechanical energy dissipates into heat via a turbulent cascade are complex and nonuniversal, with important consequences for the partition of heat between different species and directions. Recent theory has argued that in some parameter regimes a barrier to the turbulent cascade of energy forms at small scales, profoundly altering the nature of the heating of the plasma by changing how fluctuations dissipate. The solar wind is an environment, when in this parameter regime, where such a barrier would be expected to form. Here, using data from NASA’s Parker Solar Probe, we find that the shape of the magnetic energy spectrum around ion scales varies with solar wind parameters in a manner consistent with the presence of the barrier. This allows us to identify critical values of parameters necessary for the barrier to form; we show that the barrier appears fully developed for ion plasma beta of below ≃0.5 and becomes increasingly prominent with increasing normalized cross helicity (the difference in energy in wave packets propagating parallel and antiparallel to the background magnetic field) for values greater than ≃0.4. As these conditions are frequently met in the solar wind, particularly close to the Sun, our results suggest that the barrier is likely playing a significant role in turbulent dissipation in the solar wind and so is an important mechanism in explaining its heating and acceleration.